1996
DOI: 10.1046/j.1365-3083.1996.d01-303.x
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of CD80 and CD86 Molecules for Antigen Presentation by Eosinophils

Abstract: The authors analysed the antigen-presenting ability of eosinophils purified from peritoneal exudate cells of interleukin-5 (IL-5) transgenic mice. The granulocyte-macrophage colony-stimulating factor (GM-CSF)-treated eosinophils induced proliferative responses of primed lymph node T cells and thymus T cells to staphylococcal enterotoxin B (SEB), while untreated eosinophils induced little or no response. GM-CSF-treated eosinophils also induced proliferation of ovalbumin (OVA)-primed lymph node T cells to OVA. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
51
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 23 publications
10
51
0
Order By: Relevance
“…Recently, we have observed eosinophils in PBLN (44) and these leukocytes are known to act as APC (45,46). Furthermore, the function of eosinophils as an important depot of cytokines would be expected to be enhanced in the bronchial mucosa in which these cells have a more predominant profile.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have observed eosinophils in PBLN (44) and these leukocytes are known to act as APC (45,46). Furthermore, the function of eosinophils as an important depot of cytokines would be expected to be enhanced in the bronchial mucosa in which these cells have a more predominant profile.…”
Section: Discussionmentioning
confidence: 99%
“…An explanation for this phenomenon could be that cytokines secreted by allergic lung cells could up-regulate MHCII expression on eosinophils. Several cytokines like IFN-␥, IL-3, and GM-CSF secreted by inflammatory cells are reported to induce MHCII expression in vitro (5,17,19). In support of this, eosinophils from the peritoneal cavity of IL-5 Tg mice that were purified using Percoll gradients and adherence steps were reported to have no MHCII expression, except when cultured with GM-CSF (19).…”
Section: Figure 4 Sorting Eosinophils From Balf Cells Were Sorted Amentioning
confidence: 95%
“…Several cytokines like IFN-␥, IL-3, and GM-CSF secreted by inflammatory cells are reported to induce MHCII expression in vitro (5,17,19). In support of this, eosinophils from the peritoneal cavity of IL-5 Tg mice that were purified using Percoll gradients and adherence steps were reported to have no MHCII expression, except when cultured with GM-CSF (19). Others showed that BALF eosinophils isolated using Percoll gradients and adherence culture weakly expressed MHCII, probably because of GM-CSF release in vivo (7).…”
Section: Figure 4 Sorting Eosinophils From Balf Cells Were Sorted Amentioning
confidence: 99%
“…Conventionally associated with host defense against parasitic infection, through degranulation and release of toxic proteins, eosinophils also produce a variety of pro-and anti-inflammatory cytokines, growth factors, and chemokines (10 -13). Eosinophils can act as APC (14,15) and express several important costimulatory molecules (11,16), indicating that they could modulate adaptive immune responses. Eosinophils marginated in respiratory, gut, and urogenital subepithelium represent 95% of the total population, yet their physiological role is unclear.…”
mentioning
confidence: 99%